2011
DOI: 10.1111/j.1743-6109.2011.02330.x
|View full text |Cite
|
Sign up to set email alerts
|

Gepirone-ER Treatment of Low Sexual Desire Associated with Depression in Women as Measured by the DeRogatis Inventory of Sexual Function (DISF) Fantasy/Cognition (Desire) Domain—A Post Hoc Analysis

Abstract: Introduction Gepirone-extended release (ER) is effective in treating hypoactive sexual desire disorder (HSDD), as measured by the percent of females with HSDD that no longer met criteria for HSDD treatment. Another approach is to determine treatment effect on sexual desire using a recognized rating scale for sexual function. Because gepirone-ER has antidepressant and anxiolytic effects, investigation of these effects on sexual desire is appropriate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…The results presented here constitute a fairly complete analysis of the effect of depression on a [19][20][21][22]. Group C = vertical dash pattern = severe depression (HAMD-17 [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results presented here constitute a fairly complete analysis of the effect of depression on a [19][20][21][22]. Group C = vertical dash pattern = severe depression (HAMD-17 [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of sexual dysfunction was not an entry criterion for any of these studies. While sexual function measures were employed, this was not the focus of the investigations and, as a result, did not cause a high placebo response in measures of sexual function [21]. Generally, the population is made of women with an average age of 38 years old, 85% premenopausal and 81% white.…”
Section: Discussionmentioning
confidence: 99%
“…5HT 1A antagonism (Moreau et al ., ) and agonism (Brunelli et al ., ) have been shown to both be anxiolytic and anxiogenic in different models (Table ). While this probably suggests the presence of unknown interactions that modify the action at 5HT 1A , it is notable that buspirone and gepirone, 5HT 1A partial agonists, can improve both anxiety and depression (Robinson et al ., ; Yocca, ; Amsterdam, ; Fabre et al ., ). Some of the SGAs have partial agonist actions at 5HT 1A .…”
Section: Guiding Principle I: All Sgas May Have Anxiolytic Effectsmentioning
confidence: 97%
“…In premenopausal women, gepirone‐ER has shown efficacy in a depressed population as measured by reversing the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM‐IV) diagnosis of hypoactive sexual desire disorder (HSDD) [24]. Gepirone‐ER has also shown efficacy in improving DeRogatis Inventory of Sexual Function (DISF) scores in both short‐term and longer‐term studies in populations of depressed women [25].…”
Section: Introductionmentioning
confidence: 99%
“…An examination of the effect of gepirone‐ER on sexual function in women indicated that there are three components to its therapeutic profile: an antidepressant effect, an anxiolytic effect, and a pro‐sexual effect [25]. The combination of these three effects results in a statistically significant improvement in sexual function in women in both short‐term and long‐term studies.…”
Section: Introductionmentioning
confidence: 99%